Frecuencia de la posición de terceros molares inferiores retenidos no erupcionados con relación a la clasificación Pell & Gregory - Acevedo Castellanos, Pablo Enrique; Pascuas Garzón, Rafael Alberto (Universidad Antonio Nariño, 2022)
: Exodontia of the third molar is one of the most practiced procedures at the level of oral maxillofacial surgery, this is presented because the location of the mandibular third molar can vary with respect to the bony structures present.